Add-on saxagliptin improves glycemic status among uncontrolled type 2 diabetes mellitus - Pradhan, Butungeshwar; Majhi, Chakradhar; Sahu, Madhusmita (International Journal of Research in Medical Sciences, 2018)
Background: Type 2 diabetes mellitus (T2DM) have multiple pathophysiologic defects contributing to hyperglycemia. T2DM patients have insulin resistance with progressive β-cell failure and progressive insulin secretion defect. Dipeptidyl peptidase-4 (DPP-4) inhibitors target the incretin system. saxagliptin is a DPP-4 inhibitor slowing the degradation of Glucagon-like peptide-1 (GLP-1) and Glucose-dependent insulinotropic peptide (GIP) sustain the incretin effects. Aim was to know the add-on effects of saxagliptin among uncontrolled T2DM. Methods: A total of 71 uncontrolled T2DM patients on various antidiabetic therapies except incretin mimetic were consecutively selected for the study. Baseline fasting plasma glucose (FPG), 2hour postprandial glucose (PPG) and glycated hemoglobin (HbA1c) was measured. Saxagliptin orally 5mg/day was given after approval of ethical committee and FPG, 2hour PPG and HbA1c was measured at 12 weeks and 24 weeks. Data were collected and analyzed by ‘t’ test using SPSS software version 25. Results: Baseline FPG, 2hour PPG and HbA1c was 158.4±13.9mg%, 252.6±24.4mg% and 8.6±1.3% respectively. Percentage of patients achieved HbA1c of <7% at 12 weeks was 16.9% and 43.6% at 24 weeks (P <0.05). Adjusted mean difference in HbA1c was 0.73% at 12 weeks and 1.2 % at 24 weeks (P <0.05). Reduction of mean FPG, 2hour PPG and HbA1c was 154.48±13.8mg%, 240.31±26.8mg% and 7.93±1.1% at 12 weeks and 151.15±13.7mg%, 231.7±27mg% and 7.38±1% at 24 weeks respectively (P <0.05). Patients on insulin were better responded. Conclusions: Add-on saxagliptin improves all parameter of glycemic status in uncontrolled type 2 DM patients.